The Impact of COVID-19 on Protected Areas : A Systematic Review - Molteni, Carla (2021)
Understanding the effects of COVID-19 on protected areas (PAs) is very important because these spaces are crucial for international policies for biodiversity conservation and sustainable development. Therefore, the aim of this paper was to fully understand the impacts of COVID-19 on terrestrial and marine protected areas (PAs). To address this concern, we conducted a systematic review on the literature of the impacts of the pandemic on PAs. We used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines which helps authors to follow certain specific criteria when they make a systematic review on a topic. Following it, we examined five databases, together with complementary search perform in Google Scholar. Lastly, we made a qualitative assessment of articles retrieved, studying short-term changes, and identifying positive and negative effects, as well as challenges and opportunities that arise. After identifying, screening, and selecting, we included 14 journal articles published between February 2020 and May 2021. In the results we showed how the new virus-related restrictions affected the ecological, social and management dimensions of PAs. We discuss how these conserved areas gained social relevance during the pandemic but, at the same time, the vulnerability of related actors increased. Also, we suggested that some social problems differed between develop and developing countries. Additionally, digital tendencies consolidated in PAs management, research, and engagement. Overall sustainability of these places was compromised. We concluded that COVID-19 made humans to see everything through the lenses of health and PAs were not the exception.